The Application and Challenge of Chinese Folk Literature in International Chinese Language Education Under The Background of The Belt and Road Initiative: 一带一路 背景下中国民间文学在国际汉语教育中的应用与挑战 - Shan Shan, Li (Mandarinable: Journal of Chinese Studies, 2024)
With the promotion of the "Belt and Road" initiative, the importance and urgency of the transition from language teaching to culture teaching in international Chinese language education has become more and more prominent. The purpose of this paper is to explore the application value and practical challenges of Chinese folklore in international Chinese language education. Through reviewing, combing and integrating and analyzing the literature, we point out the role of Chinese folklore in international Chinese language education, as well as its problems and possible solutions in practice, on the basis of the definitions, classifications and characteristics of folklore. It is found that Chinese folklore has unique value in enhancing language skills, spreading Chinese culture, and innovating teaching methods, but in concrete practice, it is necessary to fully examine the cultural taboos among different countries and ethnic groups, develop more targeted teaching materials, and do a good job in teacher training and classroom design.